2013
DOI: 10.1016/j.juro.2012.11.046
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Vesicular Glutamate Transporters in Sensory and Autonomic Neurons Innervating the Mouse Bladder

Abstract: Purpose VGLUTs, which are essential for loading glutamate into synaptic vesicles, are present in various neuronal systems. However, to our knowledge the expression of VGLUTs in neurons innervating the bladder has not yet been analyzed. We studied VGLUT1, VGLUT2 and VGLUT3 in mouse bladder neurons. Materials and Methods We analyzed the expression of VGLUT1, VGLUT2 and calcitonin gene-related peptide by immunohistochemistry in the retrograde labeled primary afferent and autonomic neurons of BALB/c mice after i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(54 citation statements)
references
References 30 publications
0
53
1
Order By: Relevance
“…Thus, rodent sciatic nerve- (Brumovsky et al 2007; Oliveira et al 2003; Seal et al 2009), as well as urinary bladder- (Brumovsky et al 2012b) or colorectum-projecting DRG neurons (Brumovsky et al 2011b) express the three known VGLUTs (types 1, 2 and 3). VGLUT2 is by far the most widely expressed VGLUT in visceral and non-visceral DRG neurons of all sizes, followed by VGLUT1 in large and medium-sized neurons, and VGLUT3 primarily in small ones (see Brumovsky 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, rodent sciatic nerve- (Brumovsky et al 2007; Oliveira et al 2003; Seal et al 2009), as well as urinary bladder- (Brumovsky et al 2012b) or colorectum-projecting DRG neurons (Brumovsky et al 2011b) express the three known VGLUTs (types 1, 2 and 3). VGLUT2 is by far the most widely expressed VGLUT in visceral and non-visceral DRG neurons of all sizes, followed by VGLUT1 in large and medium-sized neurons, and VGLUT3 primarily in small ones (see Brumovsky 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Seven days after axotomy ( n = 13) or sham surgery ( n = 11), mice were deeply anaesthetized with chloral hydrate (350 mg/kg; Biopack, Buenos Aires, Argentina) and perfused via the ascending aorta with 20 ml warm (37 °C) Tyrode’s buffer, followed by 20 ml of a mixture of 4 % paraformaldehyde and 0.2 % picric acid in 0.16 M phosphate buffer (pH 6.9, 37 °C) and 50 ml of the same fixative at 4 °C, the latter passed in approximately, 5–7 min, as previously described (Brumovsky et al 2012a, b). The ipsilateral and contralateral L4-5, L6-S1 and S2 DRGs, as well as the corresponding levels of the spinal cord, were removed and postfixed in the same fixative for 90 min at 4 °C.…”
Section: Methodsmentioning
confidence: 99%
“…Immunohistochemical studies reveal that bladder afferent neurons contain various neuropeptides such as substance P (SP), calcitonin gene-related peptide (CGRP), pituitary adenylate cyclase-activating polypeptide (PACAP), and VIP (162,321, 394, 659, 660) as well as putative excitatory amino acid transmitters, glutamic and aspartic acid (323), and vesicular glutamate transporters (82). Peptide-containing axons are distributed throughout all layers of the bladder but are particularly dense in the lamina propria just beneath the urothelium.…”
Section: Peripheral Nervous Systemmentioning
confidence: 99%
“…VGLUT 1 -IR DRG neurons, either nonvisceral [48, 53, 54] or visceral [61, 62] appear to be nonpeptidergic and lacking IB4 (Figure 1, Table 4) or TH (Figure 2), as shown in rat [48] and mouse [53, 54, 61, 62]. Li et al [46] and Alvarez et al [50], however, have reported that VGLUT 1 may be found in neuropeptide containing afferents terminating in the laminae I and II of the rat dorsal horn.…”
Section: Expression Of Vgluts In Peripheral Visceral and Nonviscermentioning
confidence: 99%
“…Accordingly, in visceral DRG neurons targeting either the colorectum (Figure 1) or the urinary bladder [62], VGLUT 3 has only been detected in the nonpeptidergic subpopulation (Table 4). …”
Section: Expression Of Vgluts In Peripheral Visceral and Nonviscermentioning
confidence: 99%